Re-iGATE - Aysyah Pebriani, Disman (Universiti Malaysia Perlis (UniMAP), 2015)
The 6th International Engineering Invention & Innovation Exhibition 2015 (i-ENVEX 2015) was organized by ENVEX Young Researcher Club (EYReC), University Malaysia Perlis (UniMAP) and Ministry of Higher Education (MOHE), Malaysia on 17th - 19th April 2015, at UniMAP Main Campus, Pauh Putra, Perlis.